PhbZIP2 regulates photosynthesis-related genes in an intertidal macroalgae, Pyropia haitanensis, under stress - Zhang, Han; Zeng, Gaoxiong; Xie, Jiajia; Zhang, Yichi; Ji, Dehua; Xu, Yan; Xie, Chaotian; Wang, Wenlei (Frontiers in Molecular Biosciences, 2024)
Intertidal macroalgae are important research subjects in stress biology. Basic region-leucine zipper transcription factors (bZIPs) play an important regulatory role in the expression of target genes under abiotic stress. We herein identified a bZIP2 gene PhbZIP2 to regulate abiotic stress tolerance in Pyropia haitanensis, a representative intertidal macroalgal species. Cloning and sequencing of the cDNA characterized a BRLZ structure and an α coiled-coil structure between amino acids and Expression of PhbZIP2 was detected to upregulate under both high temperature and salt stresses. A DAP-seq analysis revealed the PhbZIP2-binding motifs of (T/C)TCCA(C/G) and A(A/G)AAA(G/A), which differed from the conserved motifs in plants.Overexpression of PhbZIP2 was indicative of a high temperature and salt stress tolerances in transgenic Chlamydomonas reinhardtii. It was suggested that PhbZIP2 was probably involved in regulating expression of the photosynthetic-related genes and the response to the abiotic stresses in P. haitanensis, which provide new insights for elucidating efficient adaptation strategies of intertidal macroalgae.